PATIENTS USED THE OUR VOICE CITIZEN SCIENCE FRAMEWORK TO IMPROVE A GERIATRIC REHABILITATION UNIT. (16th November 2018) - Gardiner, P; Sam, L; Tan, V; Sam, L; Tuckett, A
Abstract: With a move towards patient centred care, it is important to understand and improve the features of geriatric rehabilitation units that enhance or detract patients' experiences. Ten rehabilitation unit patients (eight in wheelchairs) used the Our Voice Citizen Science Framework to discover, discuss, advocate and change. In the discovery phase, ten citizen scientists used a mobile application (Discovery Tool app) on a tablet to record photos and audio to document features that helped or hindered their rehabilitation. In the discuss phase, seven citizen scientists met and shared their findings, identify issues and brainstorm solutions. In the advocate phase, two citizen scientists presented their findings and advocated for improvements to senior staff. Staff communicated changes to the unit that occurred in the change phase. 33 images were allocated into themes: facilities/equipment - seven positive and six negative; wheelchair access - one positive and nine negative; cleanliness - one negative; food - three positive; staff - one positive; and, nature - six positive. The majority of issues requiring intervention were related to wheelchair access or the facilities. The citizen scientists recommended simple solutions such as modifications to furniture as well as identifying potential sources of funding. New curtains have been installed and the patient kitchen moved to a more accessible area, with further modifications to the unit planned. Patients acting as citizen scientists were able to improve a rehabilitation unit. Recommendations for rehabilitation units from the citizen scientists included: conduct audits for wheelchair accessibility and incorporate green space or views.